Intensive Treatment of Cellulite Based on Physiopathological Principles - José Maria Pereira de Godoy; Mayra Yara Groggia; Lucilene Ferro Laks; Maria de Fátima Guerreiro de Godoy (Dermatology Research and Practice)
Aim. The aim of this paper is to report a novel intensive therapy of gynoid lipodystrophy (cellulite) based on a new hypothesis. Methods. Were evaluated in 10 patients with ages ranging between 25 and 59 years (mean 35.6 years) grade IV cellulite identified by clinical evaluation. Before initiating treatment, perimetry was performed at 5 cm intervals along both thighs, at the gluteal fold, 5, 10, and 15 cm above the gluteal fold, at the navel, and 5 cm above the navel. The patients were submitted to a 4-hour daily treatment session that consisted of manual and mechanical lymph drainage and cervical stimulation by the Godoy & Godoy technique adapted for the treatment of cellulite. After 10 sessions over two weeks, the patients were again evaluated. The paired t-test was utilized for statistical analysis with an alpha error of 5% (P value < 0.05). A reduction was identified at all of the measurement points (paired t-test; P value < 0.0001). Results. The mean reductions varied between 4.0 and 5.7 cm at the measurement points but reductions of more than 10 cm in perimeter were achieved in some patients. Conclusion. This technique involving lymphatic system stimulation is efficacious in the treatment of cellulite.